Analisis Sentimen pengguna Twitter terhadap Vaksinasi Sinovac dan AstraZeneca menggunakan Algoritma CART - Rani Metivianis; Dian Eka Ratnawati; Bayu Rahayudi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The first case of Covid-19 appeared in Indonesia on March 2, 2020 which caused various diseases that interfere with the respiratory system in humans. With the Covid-19 prevention strategy by requiring the public to vaccinate. Vaccines are substances that form a weakened immune system and can form antibodies for those who have not been exposed to the COVID-19 virus. There are various kinds of vaccines in Indonesia, namely Sinovac, AstraZeneca, Prifzer-BioNtech, Moderna, Sinopharm, Johnson & Johnson, CaSino, Spuntnik V. In this study, two types of vaccines were widely discussed by netizens, namely Sinovac and AstraZeneca. Sinovac is the first vaccine in Indonesia which has become a national vaccination program, while the AstraZeneca vaccine is ranked second after the Sinovac vaccine which was discussed by netizens due to the halal-haram debate on the AstraZeneca vaccine. This study aims to analyze public opinion on the Sinovac vaccine and Astrazeneca vaccine in Indonesia. Analysis was carried out on 671 tweets related to the Sinovac vaccine and Astrazeneca vaccine using the Classification and Regression Tree (CART) algorithm. Based on the results of tests and analyzes that have been carried out, with a comparison of training data and test data of 80%:20% with precision, 77%, recall 75%, f1 score 76%, and accuracy 76%.